2014
DOI: 10.1542/peds.2013-4260
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Measles in an Undervaccinated Community

Abstract: Measles is readily spread to susceptible individuals, but is no longer endemic in the United States. In March 2011, measles was confirmed in a Minnesota child without travel abroad. This was the first identified case-patient of an outbreak. An investigation was initiated to determine the source, prevent transmission, and examine measles-mumpsrubella (MMR) vaccine coverage in the affected community. Investigation and response included case-patient follow-up, post-exposure prophylaxis, voluntary isolation and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 16 publications
2
65
0
1
Order By: Relevance
“…Much can be learned from measles outbreaks, especially in describing pockets of under-immunized people that may require targeted preventive efforts, 27 and in documenting response strategies that were successful in limiting measles spread. Data from elimination settings indicate that the characteristics of unvaccinated populations are diverse; they may be faith-based groups, 12 ethnic subpopulations, 14 , 28 and certain age-cohorts 29 or members of a socioeconomic strata 30 that experienced lower immunization coverage historically. As such, preventive and response measures should be tailored to each population to be effective.…”
Section: Outbreak Response Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Much can be learned from measles outbreaks, especially in describing pockets of under-immunized people that may require targeted preventive efforts, 27 and in documenting response strategies that were successful in limiting measles spread. Data from elimination settings indicate that the characteristics of unvaccinated populations are diverse; they may be faith-based groups, 12 ethnic subpopulations, 14 , 28 and certain age-cohorts 29 or members of a socioeconomic strata 30 that experienced lower immunization coverage historically. As such, preventive and response measures should be tailored to each population to be effective.…”
Section: Outbreak Response Activitiesmentioning
confidence: 99%
“…Such analysis can be strengthened greatly by having both numerator and denominator data on the number vaccinated. This enables coverage to be calculated for specific communities, such as groups that are under vaccinated due to religious or philosophical reasons, 14 and efforts should be made to develop such data as these data are not widely available. Costs incurred by the public health sector during the response, or even a full economic evaluation, are also of interest.…”
Section: Outbreak Response Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…One study in Minnesota revealed that measlesmumps-rubella (MMR) vaccination coverage in Somali children was initially greater than in non-Somali children but subsequently declined (from 91% in 2004 to 54% in 2010) and was much lower than in nonSomali children by the end of the study period. 4 This decline was attributed to the perceptions in the Somali community that SomaliAmerican children have high rates of autism and that the MMR vaccine causes autism. [4][5][6] This decline in MMR vaccination uptake among Somali children was associated with a large measles outbreak in Minnesota.…”
mentioning
confidence: 99%